420 Anniversary of the Faculty of Philosophy in Vilnius University - Plečkaitis, Romanas (Problemos, 2000)
In general the quality of philosophy in Vilnius University (founded in 1579) was quite comparable to that of other Jesuit universities in Western Europe. The dominant philosophical school was Scholasticism. In the Faculty Philosophy in Vilnius University alongside with other science the following branches of philosophy were taught: logic, physics or the natural philosophy, metaphysics, ethics and politics. Ideas, closely related to beginnings of mathematical logic, brought to light. The most courageous lectures tried to acquaint their students with achievements in philosophy and natural sciences of the epoch of Renaissance and Modern times. A new stage in the development of philosophy began with the spread of philosophy of the epoch of Enlightenment. The conditions for the development of professional philosophy emerged in period of independent state. The Soviet occupation of Lithuania destroyed the tradition of philosophy. Only in 1989 Faculty of Philosophy in Vilnius University was re-established.